Effect of integrated nutrient management in coconut on eriophyid mite, Aceria guerreronis in different agroclimatic regions - Srinivasan, T; Rao, N B V Chalapathi; Gurav, S S; Mohan, Chandrika; Maheswarappa, H P (Indian Journal of Plant Protection, 2020)
Coconut eriophyid mite, Aceria guerreronis Keifer, is a serious pest of coconut in almost all coconut growing states of the country. Damage by the mites results in copra yield reduction to the tune of 20 – 30%. Field experiments were conducted in three coconut growing states viz., Tamil Nadu, Andhra Pradesh and Maharashtra to study the effect of Integrated Nutrient Management (INM) measures along with root feeding with azadirachtin. The INM package involved adoption of phytosanitary measures, raising green manure crops like sunnhemp in the basins, application of recommended fertilizers (1.3 kg of Urea; 2.0 kg of super phosphate; 3.5 kg of potash; 200 g of borax; 5 kg of neem cake; 50 kg of well decomposed farm yard manure; 1 kg of micronutrient mixture), adequate irrigation and following soil moisture conservation measures. The results of the study revealed that, INM measures along with root feeding with azadirachtin (1%) was significantly effective in reducing the extent of nut damage and mean grade index in all the locations tested.